Engineering yeast with bifunctional minicellulosome and cellodextrin pathway for co-utilization of cellulose-mixed sugars. Issue 1 (December 2016) - Fan, Li-Hai; Zhang, Zi-Jian; Mei, Sen; Lu, Yang-Yang; Li, Mei; Wang, Zai-Yu; Yang, Jian-Guo; Yang, Shang-Tian; Tan, Tian-Wei
Abstract Background Consolidated bioprocessing (CBP), integrating cellulase production, cellulose saccharification, and fermentation into one step has been widely considered as the ultimate low-cost configuration for producing second-generation fuel ethanol. However, the requirement of a microbial strain able to hydrolyze cellulosic biomass and convert the resulting sugars into high-titer ethanol limits CBP application. Results In this work, cellulolytic yeasts were developed by engineeringSaccharomyces cerevisiae with a heterologous cellodextrin utilization pathway and bifunctional minicellulosomes. The cell-displayed minicellulosome was two-scaffoldin derived, and contained an endoglucanase and an exoglucanase, while the intracellular cellodextrin pathway consisted of a cellodextrin transporter and a β-glucosidase, which mimicked the unique cellulose-utilization system inClostridium thermocellum and allowedS. cerevisiae to degrade and use cellulose without glucose inhibition/repression on cellulases and mixed-sugar uptake. Consequently, only a small inoculation of the non-induced yeast cells was required to efficiently co-convert both cellulose and galactose to ethanol in a single-step co-fermentation process, achieving a high specific productivity of 62.61 mg cellulosic ethanol/g cell·h from carboxymethyl cellulose and 56.37 mg cellulosic ethanol/g cell·h from phosphoric acid-swollen cellulose. Conclusions Our work provides a versatile engineering strategy for co-conversion of cellulose-mixed sugars to ethanol byS. cerevisiae, and the achievements in this work may further promote cellulosic biofuel production.